Synthesis of Novel Potent Biologically Active N-Benzylisatin-Aryl Hydrazones in Comparison with Lung Cancer Drug ‘Gefitinib’ - Huda S. Al-Salem; Hatem A. Abuelizz; Iman S. Issa; Amany Z. Mahmoud; Ali AlHoshani; Md Arifuzzaman; A. F. M. Motiur Rahman (Applied Sciences, 2020)
Developing anticancer therapeutics with no/few side effects is a challenge for medicinal chemists. The absence of antibacterial activity of an anticancer drug removes its detrimental effect toward intestinal flora and therefore leads to reduced side effects. Here, a series of novel N-benzylisatin-aryl-hydrazones was designed, synthesized and evaluated for their antimicrobial and antiproliferative activities with SAR and ADME studies, aiming to develop anticancer drugs with no antimicrobial, yet high antiproliferative activities. The results were then compared with the effects of first-line treatments for lung cancer drug Gefitinib. Novel N-benzylisatin-aryl-hydrazones were synthesized from isatin and benzyl bromide in three steps with good to moderate yields. Antimicrobial activity was tested with six Gram-positive/negative bacterial strains, antifungal activity with a fungal strain and antiproliferative activity against ‘A549’ and ‘HeLa cell lines’, respectively. As expected, synthesized hydrazones reveled no effects on any of the strains of bacteria and fungi up to 100-µg/disc concentration. However, four compounds showed two-to-four fold antiproliferative activity over Gefitinib. For instance, IC50 of a compound (6c) shows concentration of 4.35 µM, whereas gefitinib shows 15.23 µM against ‘A549.’ ADME predicted studies reveled that our synthesized hydrazones exhibited higher ADME values than the Gefitinib. Therefore, our synthesized hydrazones can be an excellent scaffold for the development of anticancer therapeutics after considering further investigations.